ATIM-39. PHASE 2 OPEN-LABELED STUDY OF ADJUVANT TEMOZOLOMIDE PLUS TUMOR TREATING FIELDS PLUS PEMBROLIZUMAB IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA (2-THE-TOP). (11th November 2019) - Tran, David; Warren, Sonisha; Allen, Anne; Sampson, Deborah; Chen, Dongjiang; Thomas, Nagheme; Greene, Valerie; Rahman, Maryam; Ghiaseddin, Ashley
Abstract: BACKGROUND/OBJECTIVE: Tumor treating Fields (TTFields) plus maintenance temozolomide is an approved standard treatment for newly diagnosed Glioblastoma (GBM). TTFields are alternating electric fields of low intensity and intermediate frequency delivered non-invasively via transducer arrays to tumor region. Immune checkpoints have not been studied widely in newly diagnosed GBM patients. TTFields combined with temozolomide elicit anti-mitotic effects on proliferative cancer cells and augment recruitment of immune effector cells specific for glioma cells to the tumor microenvironment where pembrolizumab further potentiates the immune reaction to achieve a synergistic therapeutic effect. This study [NCT03405792] will determine if adding pembrolizumab to TTFields and maintenance temozolomide (triple combination) increases progression-free survival (PFS) in patients with newly diagnosed GBM versus historical control (EF-14). METHODS: This study will enroll patients (N=24) with pathologic diagnosis of newly diagnosed GBM WHO grade 4, > 18 years after maximal surgery or biopsy followed by radiation therapy with adjuvant temozolomide (Stupp protocol). The primary endpoint is increases in PFS compared to historical control data (EF-14). Secondary endpoints include: toxicity and tolerability of the triple combination; overall survival and response rates versus historical data; augmentation of TTFields-initiated glioma-specific immune reaction by pembrolizumab. Exploratory endpoints include: metabolomics signature of immune activation by TTFields and TTFields plus pembrolizumab in serum and urine, and correlation of mutation burden in primary tumor samples with response to pembrolizumab plus TTFields. We assumed an accrual period of 12 months, an accrual rate of 2 patients per month, an additional 18 months of follow-up, and proportional hazards. Per shape parameter estimate of k=0.88 with empirical 95% confidence interval (0.82, 0.95) obtained via simulation of historical control data, a sample size of 24 patients should detect an improvement in PFS of 6 to 8 months with 80% power and a 1-sided significance level of 0.05 (Wu and Xiong, 2014).